2007
DOI: 10.1128/jvi.02128-06
|View full text |Cite
|
Sign up to set email alerts
|

Natural Antibody and Complement Mediate Neutralization of Influenza Virus in the Absence of Prior Immunity

Abstract: Early control of virus replication by the innate immune response is essential to allow time for the generation of a more effective adaptive immune response. As an important component of innate immunity, complement has been shown to be necessary for protection against numerous microbial infections. This study was undertaken to investigate the role of complement in neutralizing influenza virus. Results demonstrated that the classical pathway of complement mediated serum neutralization of influenza virus. Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
211
0
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(239 citation statements)
references
References 36 publications
14
211
0
8
Order By: Relevance
“…Only a single IgM molecule is needed to activate the hemolytic activity of complement, a task that requires roughly 1,000 IgG molecules (11). Natural antibodies and subsequent complement activation cause the lysis or neutralization of many viruses (21,22,38,42,51,52,61). However, we were unable to detect any neutralizing effect of 90% mouse serum on the infectious titer of Ad vectors (our unpublished observations), in agreement with a previous report (2).…”
Section: Vol 82 2008 Mechanisms For Uptake Of Adenovirus By Kupffersupporting
confidence: 74%
See 1 more Smart Citation
“…Only a single IgM molecule is needed to activate the hemolytic activity of complement, a task that requires roughly 1,000 IgG molecules (11). Natural antibodies and subsequent complement activation cause the lysis or neutralization of many viruses (21,22,38,42,51,52,61). However, we were unable to detect any neutralizing effect of 90% mouse serum on the infectious titer of Ad vectors (our unpublished observations), in agreement with a previous report (2).…”
Section: Vol 82 2008 Mechanisms For Uptake Of Adenovirus By Kupffersupporting
confidence: 74%
“…Similar findings have previously been made with a number of other viruses (21,22,37,61). Although the monomeric affinity of natural IgM tends to be much lower than that of affinity-matured antigen-specific IgG antibodies, the avidity of IgM can be very high when bound to repetitive antigens (such as viral capsids), because IgM is a pentamer or a hexamer that contains 10 or 12 Fabs (69).…”
Section: Vol 82 2008 Mechanisms For Uptake Of Adenovirus By Kupffersupporting
confidence: 56%
“…We provide evidence that the reason for the much more efficient transport of viral particles lies in the presence of natural Abs. Unspecific nIgM Abs present in serum of naive animals have been shown to bind a number of pathogens (36)(37)(38)43). They represent an innate defense mechanism and play an important role in protection from viral and bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of specific immunity, the classical pathway can be activated by so-called natural IgM (nIgM) Abs that are produced without previous exposure to foreign Ag. Several reports have shown that sera from naive mice contain low-affinity nIgM Abs that bind to viruses and bacteria and are important for neutralizing these pathogens (36)(37)(38)(39). The reduced Ag deposition in C1q-deficient mice suggested that nIgM may also play a role in Ag transport.…”
Section: Natural Abs Mediate Transport Of Particulate Agmentioning
confidence: 99%
“…Natural IgM antibodies are constitutively secreted by B1 cells. Several elegant animal models have demonstrated the protective role of natural IgM against numerous viral, bacterial, and parasitic infections (Influenza, Pseudomonas aeruginosa, Plasmodium falciparum) and a worse outcome of patients with IgM deficiency [5][6][7]. IgM has an important role in the classical pathway of complement activation when complexed with antigens and its pentameric structure favors agglutination of the invading organism and its neutralization.…”
mentioning
confidence: 99%